2019
DOI: 10.1002/ijc.32593
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifier gene mutations‐positive AML patients with intermediate‐risk karyotypes benefit from decitabine with CAG regimen

Abstract: It remains unclear whether there is a relationship between therapeutic effects of hypomethylating agents (HMAs) and epigenetic modifier gene mutations (EMMs) in patients with cytogenetically intermediate‐risk acute myeloid leukemia (IR‐AML). Based on targeted‐capture sequencing, we retrospectively analyzed the correlation between EMMs and prognosis in 83 IR‐AML patients treated with decitabine in combination with cytarabine, aclarubicin hydrochloride and granulocyte colony‐stimulating factor (DCAG, n = 35) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…These results suggested that decitabine‐based regimens might improve the unfavorable impact of DNMT3A and TP53 mutations. In line with our data, Xu et al suggested that AML patients with epigenetic modifier gene mutations, including DNMT3A , tended to have better survival when treated with decitabine‐based regimens compared to standard induction chemotherapy 27 . TP53 mutation was reported to be correlated with exceedingly adverse outcomes under intensive chemotherapy modality 28 .…”
Section: Discussionsupporting
confidence: 90%
“…These results suggested that decitabine‐based regimens might improve the unfavorable impact of DNMT3A and TP53 mutations. In line with our data, Xu et al suggested that AML patients with epigenetic modifier gene mutations, including DNMT3A , tended to have better survival when treated with decitabine‐based regimens compared to standard induction chemotherapy 27 . TP53 mutation was reported to be correlated with exceedingly adverse outcomes under intensive chemotherapy modality 28 .…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the ORR of DCAG chemotherapy was 76.9%, and 69.2% of patients achieved CR, which showed obvious advantage when compared with standard chemotherapy or palliative treatment. Most patients in our study who were effective with DCAG chemotherapy regimen contained epigenetic modifier gene mutations like IDH1/ IDH2, ASXL1, TET2 or DNMT3A mutations, and this was consistent with our team's previous research [53]. However, due to the limited sample, there were no statistically genetic subgroups that could be most effective with DCAG regimen for these elderly patients.…”
Section: Discussionsupporting
confidence: 89%
“…However, no specific promoter methylation change was found to be correlated with therapy response to HMAs (Issa et al, 2004). While a retrospective study of intermediaterisk patients confirmed a significant positive relationship between epigenetic modifier gene mutations and clinical response to HMAs (Xu et al, 2020a). Consistent with the phenomenon that genetic mutations of DNA methylation regulators contribute to a remarkable change in DNA methylation profiles (Delhommeau et al, 2009).…”
Section: Clinical Significance Of Restoring Dna Methylation In T(8;21...mentioning
confidence: 94%